Enhancement of carbamazepine removal rate using Tetradesmus obliquus KNUA061 and NaOCl and utilization of the resulting biomass - Do, Jeong-Mi; Yeo, Hee-Tae; Do, Geum-Sook; Hong, Ji Won; Yoon, Ho-Sung (Frontiers in Energy Research, 2022)
The diversification of pharmaceutical industries has led to intense concern about the possible treatment methods for various newly emerging micropollutants. In order to remove CBZ, a widely used substance frequently detected in water body, a preliminary experiment was conducted with indigenous microalgae isolated from a primary settled wastewater treatment plant. The T. obliquus strain KNUA061 was then selected for further testing. In order to increase CBZ removal efficiency, NaOCl, which is mainly used in the water purification process, was utilized as an external stimulus to increase the removal rate by up to 80%. A rapid growth rate and high biomass productivity of approximately 3 g L-1 were accomplished via the use of an appropriate concentration. Roughly 90% CBZ was present during the removal process with less than 10% being converted to secondary metabolites. As confirmed by antioxidant enzyme activity, degree of lipid oxidation, and amino acid content, the antioxidant system activity in assorted pathways was increased due to the NaOCl treatment. Regarding biomass analysis, a relatively high HHV compared with crops and lignocellulosic materials was confirmed, resulting in its establishment as a possible renewable energy source. However, poor biodiesel properties were obtained due to the high PUFA content including α-linolenic acid (C18:3 ω 3). Nevertheless, it was determined that the microalgal biomass has acceptable feasibility as a sustainable dietary supplement feedstock due to its abundant protein and essential amino acid contents